Theoretical Model for Prediction of Durable Life of RC Square Piles under Marine Environment. Issue 5 (September 2019) - Xu, Qiuhong; Shi, Danda; Shao, Wei
Abstract: This paper presents a model for predicting the durable life of reinforced concrete (RC) square piles under marine environment. Firstly, according to Fick's first law and mass conservation law, the diffusion equation of chloride ion in RC square pile is established, and found the analytical solution of the diffusion equation; secondly, the critical rust depth of the concrete cover is generated according to Faraday's law. Finally, the purpose of predicting the durable life of RC square piles is achieved.